Advanced flow cell design for in vitro release testing of mucoadhesive buccal films - Grilc Blaž; Zdovc Jurij; Planinšek Odon (Acta Pharmaceutica)
Films for buccal application are a slowly emerging new platform for drug delivery. There remains a lack of analytical techniques for the determination of in vitro active pharmaceutical ingredient release. The aim here was to develop an alternative method to the commonly used United States Pharmacopoeia (USP) 2 method, based on the flow-through cell. This system extends the release time and enables more detailed sample discrimination according to formulation. It could be used as a tool for in vivo prediction of drug release rates from buccal film formulations. The flow cell contains two chambers separated by a membrane through which the released active pharmaceutical ingredient is measured. Vital system variables and their effects on the release rate of the model active pharmaceutical ingredient are presented for formulations based on sodium alginate polymer. The method reflects the differences between films and is shown to be discriminatory for evaluation of buccal formulations.